Comparative Analysis of Financial Reporting under PSAK 73 and PSAK 30: Implications for Lease Accounting Practices - Wiyarti, Evy Steelyana; Fadlurahman, Muhammad Harris (INVENTORY: JURNAL AKUNTANSI, 2024)
The purpose of this study was to determine the differences in the presentation of  financial statements in the implementation of PSAK 30 and PSAK 73 and to analyze  the company's performance after the implementation of PSAK 73. The method used in  this study was a qualitative method with descriptive analysis. In this study, interviews  and data collection were conducted. The data and information obtained are processed  by comparison and ratio calculation. The results of the study are the differences  between the implementation of PSAK 30 and PSAK 73 at PT. KBS  can be directly seen in the increase in total assets, total liabilities and total  equity. In the calculation of the ratio, several results show an increase in value after  the application of PSAK 73. It is concluded that since the application of PSAK 73, the  company's performance has increased and financial reporting has become more  efficient and transparent.